Cross-section behavior of cold-formed steel elliptical hollow sections – A numerical study. (15th December 2019) - Yao, Ye; Quach, Wai-Meng; Young, Ben
Highlights: A new approach to the FE modeling of CF tubular stub columns is presented. Strength enhancement and local imperfections from forming are predicted numerically. The effect of forming parameters on strength enhancement in CF steel EHS was studied. Models for strength enhancement and local imperfections in CF EHS are presented. A new slenderness limit for CF steel EHS stub columns is proposed. Abstract: The paper presents a numerical study on the stub-column behavior of cold-formed steel elliptical hollow sections (EHS). In the paper, a finite element model for the stub columns of cold-formed tubular sections is presented, in which residual stresses, strength enhancement, geometric imperfection resulting from cold forming are predicted by using a rigorous finite element simulation of the roll-forming process. The accuracy of the finite element model for stub columns was verified by comparing the numerical predictions with test results. By using the verified finite element model, a parametric study on the stub-column behavior of cold-formed steel EHS was carried out for a wide range of section sizes and steel grades (covering both normal grade steels and high strength steels). Based on the generated finite element data, predictive models for the strength enhancement and local geometric imperfection of cold-formed steel EHS are proposed. Furthermore, the cross-section classification for cold-formed steel EHS were examined according to the slenderness limits of circular hollow sections (CHS) in current design codes. It can be found that the equivalent diameter method together with the current CHS slenderness limits in existing design codes can be safely adopted for cold-formed steel EHS. In addition, a new yield slenderness limit for cold-formed steel EHS is proposed.